Mitigation Of Syn-Flooding Attack Using High Speed Programmable Network Processor - Lim, Boon Ping (2006)
Denial of service (DoS) attacks tie up resources of a remote host or network, thereby denying or degrading service to legitimate users. This thesis brings closer two emerging areas of networking, network processor and firewall system. We propose an innovative and practical SYN-flooding defense system built on network processor. An embedded architecture, called synmon (SYN-flooding monitoring) is proposed. Our solution is an end-point-based autonomous system which is deployable at both source and victim network's border routers.